Comparison between endovascular aneurysm repair-selected and endovascular aneurysm repair-only strategies for the management of ruptured abdominal aortic aneurysms: An 11-year experience at a Chinese tertiary hospital - Fang, Gang; Yue, Jianing; Shuai, Tao; Yuan, Tong; Ren, Bichen; Fang, Yuan; Pan, Tianyue; Liu, Zhenjie; Dong, Zhihui; Fu, Weiguo (Frontiers in Cardiovascular Medicine, 2022)
Objectives The aim of this study was to review our management experience of ruptured abdominal aortic aneurysms (RAAAs) using an endovascular aneurysm repair (EVAR)-only strategy, and discuss the feasibility of this strategy. Materials and methods A retrospective analysis of clinical data was performed in patients with RAAAs from January 2009 to October 2020. Our strategy toward operative treatment for RAAAs evolved from an EVAR-selected (from January 2009 to April 2014) to an EVAR-only (from May 2014 to October 2020) strategy. Baseline characteristics, thirty-day mortality, perioperative complications, and long-term outcomes of patients were compared between the two periods. Results A total of 93 patients undergoing emergent RAAA repair were eventually included. The overall operation rate in RAAAs at our centre was 70.5% (93/132). In the EVAR-only period, all 53 patients underwent ruptured endovascular aneurysm repair (rEVAR). However, only 47.5% (19/40) of patients in the EVAR-selected period underwent rEVAR, and the remaining 21 patients underwent emergent open surgery. Thirty-day mortality in the EVAR-only group was 22.6% (12/53) compared with 25.0% (10/40) for the EVAR-selected group (P = 0.79). Systolic blood pressure ≤70 mmHg [adjusted odds ratio (OR) 4.99, 95% confidence interval (CI), 1.13–22.08, P = 0.03] and abdominal compartment syndrome (adjusted OR 3.72, 95% CI, 1.12–12.32, P = 0.03) were identified as independent risk factors responsible for 30-day mortality. After 5 years, 47.5% (95% CI, 32.0–63.0%) of patients in the EVAR-selected group were still alive versus 49.1% (95% CI, 32.3–65.9%) of patients in the EVAR-only group (P = 0.29). Conclusion The EVAR-only strategy has allowed rEVAR to be used in nearly all the RAAAs with similar mortality comparing with the EVAR-selected strategy. Due to the avoidance of operative modality selection, the EVAR-only strategy was associated with a more simplified algorithm, less influence on haemodynamics, and a shorter operation and recovery time.